The effect of combining electron beam irradiation and ionic liquid soaked (ILS) pretreatment on lignocellulosic of oil palm frond (OPF): article - Mahmad Jaki, Nursyakila Suzieana; Azizan, Amizon; Jusri, Nur Amira Aida (2018)
Oil Palm Frond (OPF) is used as lignocellulosic biomass (LCB) as potential raw material for bioethanol production. This research was conducted to study the effect of combining electron beam irradiation and ionic liquid soaked (ILS) on lignocellulosic of OPF. LCB are soaked with 50% of 1ethyl-3-methylimidazolium acetate, [EMIM]Ac for ionic liquid pretreatment and then irradiated with different doses which was 100-1000 kGy using electron beam under cooperation with Agensi Nuklear Malaysia. The characterization of treated OPF was conducted by using Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD). The combination of ionic liquid soaked and electron beam irradiation on OPF was demonstrated to be more effective by the significant reduction of Lateral Order Index (LOI) (FTIR) and reduction of Crystallinity Index (CrI) (XRD). The value of LOI of ILS OPF decreased from 0.77 (untreated OPF) to 0.64 at 800 kGy doses of irradiation and the CrI value of ILS OPF also decreased from 63.99% (untreated OPF) to 55.87% at 1000 kGy doses of irradiation.